SIMULATION OF THE INFLUENCE OF FIBER VOLUME FRACTION AND FIBER ORIENTATION ON THE STRENGTH OF POLYESTER COMPOSITE REINFORCED WITH GLASS FIBER IN BENDING STRENGTH - Fakhruddin, Muhammad; Mashudi, Imam; Pramita Sari, Nurlia; Widhi Supriyanto, Nicky Suwandhy (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Fiber-reinforced composites can be classified into two parts, namely short fiber composites and long fiber composites. Long fibers are generally stronger than short fibers. Long fiber (continuous fiber) is more efficient in laying than short fiber but short fiber is easier to lay than long fiber. Fiber length affects the processability of the fiber composite. Judging from the theory, long fibers can transfer the load and stress from the stress point to the other fiber. In this research, we simulated the effects of volume fraction and fiber orientation in glass fiber-reinforced polyester composites on bending strength to examine the effect of each parameter on the mechanical properties of glass fiber composites. The mechanical properties of the composite were tested using the three-point bending and tensile testing methods. The study expects to find variations in mechanical properties with changes in the glass fiber volume fraction and fiber orientation. In this study, it is planned to function in a relevant environment, the components in this study must be able to operate properly and have been well integrated with prototype manufacturing that has been tested as a test tool function. Notably, the pinnacle of the bending test, measuring 170.41 MPa, was achieved at the specific combination of a 0.5 Fiber Volume Fraction and the 0-90o fiber orientation.